La terapia della gestalt con gli attacchi di panico Modello Relazionale di Base, ciclo vitale e clinica in GTK - 1 Gaspare Orlando (Marp Edizioni, 2020)
The article describes the study, research and clinic of Panic Attacks with a phenomenological and procedural reading, faithful to the theoretical-clinical orientation of Gestalt Therapy (gtk institute). The Panic Attacks can be considered a dramatic request for a relationship to reconstruct that constitutive belonging to every integral and full identity. In this regard, in the contribution, the issues concerning the phenomenology of the Panic Attack in the Postmodern Society will be addressed, the meaning of the symptom in relation to the patient's Life Cycle with reference to the current context and to the Base Relational Model (BRM). Study and clinical research shed light on the diagnostic aspect of panic attacks (contact interruption and body-relational experience in the retroflexive relational style), and on the therapeutic one, taking into account the contact cycle theory, the theory evolutionary and of the theory of the self. Finally, emphasis will be given to the differential diagnosis between the Panic Attack and the Panic Crisis, since this aspect determines the specific clinical and therapeutic intervention.